2012
DOI: 10.1016/j.regsciurbeco.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social capital on crime: Evidence from the Netherlands

Abstract: This paper investigates the relation between social capital and crime. The analysis contributes to explaining why crime is so heterogeneous across space. By employing current and historical data for Dutch municipalities and by providing novel indicators to measure social capital, we find a link between social capital and crime. Our results suggest that higher levels of social capital are associated with lower crime rates and that municipalities' historical states in terms of population heterogeneity, religiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 82 publications
1
41
0
1
Order By: Relevance
“…At the country and community level, for instance, social capital has a positive effect on economic performance (Neira, Portela, & Vieira, 2010), innovation (Kaasa, 2009), and health (von dem Knesebeck, Dragano, & Siegrist, 2005). Higher levels of social capital at the country level are also related to lower suicide rates (Kelly, Davoren, Mhaolain, Breen, & Casey, 2009), less crime (Akcomak & ter Weel, 2011), higher rates of education (Coleman, 1988), and political participation (Lippl, 2007), as well as to better and more effective government (Zmerli & Newton, 2008). Paralleling culture-level findings, individuals possessing more social capital tend to be healthier (e.g.…”
Section: The Relationship Between Social Capital and Individualism-comentioning
confidence: 99%
“…At the country and community level, for instance, social capital has a positive effect on economic performance (Neira, Portela, & Vieira, 2010), innovation (Kaasa, 2009), and health (von dem Knesebeck, Dragano, & Siegrist, 2005). Higher levels of social capital at the country level are also related to lower suicide rates (Kelly, Davoren, Mhaolain, Breen, & Casey, 2009), less crime (Akcomak & ter Weel, 2011), higher rates of education (Coleman, 1988), and political participation (Lippl, 2007), as well as to better and more effective government (Zmerli & Newton, 2008). Paralleling culture-level findings, individuals possessing more social capital tend to be healthier (e.g.…”
Section: The Relationship Between Social Capital and Individualism-comentioning
confidence: 99%
“…Although types of groups that people are involved in globally varies by region, participation in all these types of groups allows members to form new social networks and build the overall social capital of the community. Greater community social capital has been linked to reductions in crime (Akçomak & ter Weel, 2012), improved health outcomes (Elgar, Davis, Wohl, Trites, Zelenski, & Martin, 2011), and agricultural innovation (Heemskerk & Wennink, 2004). Shared Farming Activities: During our qualitative interviews, farmers reported that they shared their vegetables with their friends and cooperated with other farmers by helping to carry soil for their sacks or sharing seedlings.…”
Section: Social Capitalmentioning
confidence: 99%
“…A recent study on the impact of social capital analyzed regional crime rates using historical data on household, population, occupation, etc. as instrumental variables, from 1795 to 1970 (Akcomak and Weel 2008). The Netherlands Volkstellingen Archive (Dutch census) provides this data and more.…”
Section: Future Developments and Challengesmentioning
confidence: 99%